2012
DOI: 10.1029/2012sw000851
|View full text |Cite
|
Sign up to set email alerts
|

CEDAR Electrodynamics Thermosphere Ionosphere (ETI) Challenge for systematic assessment of ionosphere/thermosphere models: Electron density, neutral density, NmF2, and hmF2 using space based observations

Abstract: In an effort to quantitatively assess the current capabilities of Ionosphere/Thermosphere (IT) models, an IT model validation study using metrics was performed. This study is a main part of the CEDAR Electrodynamics Thermosphere Ionosphere (ETI) Challenge, which was initiated at the CEDAR workshop in 2009 to better comprehend strengths and weaknesses of models in predicting the IT system, and to trace improvements in ionospheric/thermospheric specification and forecast. For the challenge, two strong geomagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 37 publications
7
76
0
Order By: Relevance
“…Kwak et al (2011) investigated the influence of IMF sector polarity changes on CHAMP observations during 2003. Shim et al (2012) compared various empirical and physical models with CHAMP density during six selected storms and three quiet intervals; the empirical models were generally in better agreement with the data.…”
Section: Time-dependent Response To the Solar Wind And Imfmentioning
confidence: 71%
See 1 more Smart Citation
“…Kwak et al (2011) investigated the influence of IMF sector polarity changes on CHAMP observations during 2003. Shim et al (2012) compared various empirical and physical models with CHAMP density during six selected storms and three quiet intervals; the empirical models were generally in better agreement with the data.…”
Section: Time-dependent Response To the Solar Wind And Imfmentioning
confidence: 71%
“…Second, the thermosphere is strongly forced by external (especially solar) drivers, with little internal variability, so forecast accuracy depends in large part on forecasts of the drivers. As a result, physical and empirical models currently produce density forecasts with similar accuracy (National Research Council, 2012;Shim et al, 2012). Recent efforts to use physical models for nowcasting and forecasting are reviewed in section 5.1.…”
Section: Basic Physical Considerationsmentioning
confidence: 98%
“…IRI was one of the best performing models in the Electrodynamics Thermosphere Ionosphere (ETI) Challenge of the Coupling, Energetics, and Dynamics of Atmospheric Regions (CEDAR) program of the National Science Foundation (NSF) (Shim et al, 2011;Shim et al, 2012). IRI is acknowledged in 8% of all 2012 Journal of Geophysical Research papers and 15% of all 2012 Radio Science papers.…”
Section: Discussionmentioning
confidence: 98%
“…The standard IRI model describes average conditions quite well and has shown excellent results in comparisons with other models (Shim et al, 2011;Shim et al, 2012). IRI performance can be even more improved if observations are available for a time of interest in real-time or retrospective.…”
Section: The Real-time Irimentioning
confidence: 90%
“…The average error for JB2008 is 19.0% in the Northern Hemisphere and 19.4% in the Southern Hemisphere. Previous studies have reported that the JB2008 model generally performs slightly better than the MSISE-00 model [Bowman et al, 2008b;Shim et al, 2012]. For MSISE-00, the quiet-time densities are computed for ap = 0 nT, and the non-quiet-time densities are obtained for ap = 27 nT.…”
Section: Comparison With Other Modelsmentioning
confidence: 99%